2014
DOI: 10.1371/journal.pone.0093305
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Quantitative Proteomic Analysis of Dengue Virus Type 2 Infected A549 Cells

Abstract: Disease caused by dengue virus is a global health concern with up to 390 million individuals infected annually worldwide. There are no vaccines or antiviral compounds available to either prevent or treat dengue disease which may be fatal. To increase our understanding of the interaction of dengue virus with the host cell, we analyzed changes in the proteome of human A549 cells in response to dengue virus type 2 infection using stable isotope labelling in cell culture (SILAC) in combination with high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 94 publications
1
46
0
Order By: Relevance
“…It is well recognized that viral infections can induce significant changes in cellular proteomes [30][31][32] and an increase in protein levels during DENV infection may contribute to the increased protein capture measured by qTUX-MS. To address this, we used SILAC-MS to quantify proteome (i.e., total protein abundance) changes following DENV infection. Comparison of qTUX-MS and proteome SILAC ratios showed that the protein abundances for the 93 qTUX-MS-identified vRNA-binding factors remained largely unchanged (Fig 2A, S1 Fig and S1 Dataset).…”
Section: The Majority Of Candidate Host Factors Are Not Altered At Thmentioning
confidence: 99%
“…It is well recognized that viral infections can induce significant changes in cellular proteomes [30][31][32] and an increase in protein levels during DENV infection may contribute to the increased protein capture measured by qTUX-MS. To address this, we used SILAC-MS to quantify proteome (i.e., total protein abundance) changes following DENV infection. Comparison of qTUX-MS and proteome SILAC ratios showed that the protein abundances for the 93 qTUX-MS-identified vRNA-binding factors remained largely unchanged (Fig 2A, S1 Fig and S1 Dataset).…”
Section: The Majority Of Candidate Host Factors Are Not Altered At Thmentioning
confidence: 99%
“…These evidences show that GANAB and P4HB are relevant proteins not only in our 12 interactomes, but also in other host-pathogen systems, which confirm these proteins as possible hallmarks of the host-parasite interaction. Other host proteins common in several parasite interactomes ( Fig 7) such as HYOU1, PDIA3, HSPA9, CTSS, etc., have been already found deregulated upon pathogenic infection [78][79][80][81][82][83].…”
Section: Common Targeted Host Proteins Across Interactomesmentioning
confidence: 99%
“…The probability of finding specific biomarkers of infection very much increases with potent analytical proteomics tools used in a comprehensive and systematic approach. Advances in MS and protein identification have made possible identification and quantification of levels of cellular proteins in response to dengue virus infection [94]. Previously, the differential protein expression in serum samples from dengue-infected patients resulted in the identification of cellular proteins with potential to become targets in dengue pathogenesis [95,96].…”
Section: Future Perspectivementioning
confidence: 99%